E‐Skin Tactile Sensor Matrix Pixelated by Position‐Registered Conductive Microparticles Creating Pressure‐Sensitive Selectors. (4th June 2018) - You, Insang; Choi, Song‐Ee; Hwang, Hyejin; Han, Sang Woo; Kim, Jin Woong; Jeong, Unyong
Abstract: Electronic skin (E‐skin) imitates human skin by converting external stimuli into electrical signals. E‐skin requires high flexibility and a high level of device integration. Unlike conventional E‐skin creation methods, a highly sensitive pressure sensor matrix (100 pixels cm −2 ) made of position‐registered elastic conductive microparticles (MPs) is created. The MPs form a Schottky junction with the bottom electrode and the current through the junction is sensitive to external pressure, forming a simple one‐selector two‐terminal device array. The Schottky junction eliminates the electrical cross talks between the sensor pixels consisting of 64 MPs in each. The flexible pressure sensor matrix is used as an artificial fingertip for Braille reading and as an electronic scale based on detailed force distribution. This work opens up the possibility that assembled MPs, which have been a long‐standing research topic in academia, can be used to make practical electronic devices. Abstract : A new strategy to fabricate a pressure‐sensitive selector based on assembled microparticles is presented . Highly ordered large‐area microparticle arrays assembled through a physicochemical template become pixelated pressure‐sensitive diodes for a tactile sensor matrix. Each particle responses to the applied pressure and rectifies the current for cross talk inhibition at the same time.